The landscape of MHC-presented phosphopeptides yields actionable shared tumor antigens for cancer immunotherapy across multiple HLA alleles - Richard J O'Reilly; Zaki Molvi; Martin G Klatt; Tao Dao; Jessica Urraca; David A Scheinberg (Journal for ImmunoTherapy of Cancer, 2023)
Background Certain phosphorylated peptides are differentially presented by major histocompatibility complex (MHC) molecules on cancer cells characterized by aberrant phosphorylation. Phosphopeptides presented in complex with the human leukocyte antigen HLA-A*02:01 provide a stability advantage over their non-phosphorylated counterparts. This stability is thought to contribute to enhanced immunogenicity. Whether tumor-associated phosphopeptides presented by other common alleles exhibit immunogenicity and structural characteristics similar to those presented by A*02:01 is unclear. Therefore, we determined the identity, structural features, and immunogenicity of phosphopeptides presented by the prevalent alleles HLA-A*03:01, HLA-A*11:01, HLA-C*07:01, and HLA-C*07:02.Methods We isolated peptide-MHC complexes by immunoprecipitation from 11 healthy and neoplastic tissue samples using mass spectrometry, and then combined the resulting data with public immunopeptidomics data sets to assemble a curated set of phosphopeptides presented by 96 samples spanning 20 distinct healthy and neoplastic tissue types. We determined the biochemical features of selected phosphopeptides by in vitro binding assays and in silico docking, and their immunogenicity by analyzing healthy donor T cells for phosphopeptide-specific multimer binding and cytokine production.Results We identified a subset of phosphopeptides presented by HLA-A*03:01, A*11:01, C*07:01 and C*07:02 on multiple tumor types, particularly lymphomas and leukemias, but not healthy tissues. These phosphopeptides are products of genes essential to lymphoma and leukemia survival. The presented phosphopeptides generally exhibited similar or worse binding to A*03:01 than their non-phosphorylated counterparts. HLA-C*07:01 generally presented phosphopeptides but not their unmodified counterparts. Phosphopeptide binding to HLA-C*07:01 was dependent on B-pocket interactions that were absent in HLA-C*07:02. While HLA-A*02:01 and HLA-A*11:01 phosphopeptide-specific T cells could be readily detected in an autologous setting even when the non-phosphorylated peptide was co-presented, HLA-A*03:01 or HLA-C*07:01 phosphopeptides were repeatedly non-immunogenic, requiring use of allogeneic T cells to induce phosphopeptide-specific T cells.Conclusions Phosphopeptides presented by multiple alleles that are differentially expressed on tumors constitute tumor-specific antigens that could be targeted for cancer immunotherapy, but the immunogenicity of such phosphopeptides is not a general feature. In particular, phosphopeptides presented by HLA-A*02:01 and A*11:01 exhibit consistent immunogenicity, while phosphopeptides presented by HLA-A*03:01 and C*07:01, although appropriately presented, are not immunogenic. Thus, to address an expanded patient population, phosphopeptide-targeted immunotherapies should be wary of allele-specific differences.